An exploratory, open-label, parallel group, randomised controlled trial evaluating the effect of gene based nutritional intervention in type 2 diabetes: The protocol for NUDGE clinical trial - Savitesh Kushwaha; Poonam Khanna; Sanjay Kumar Bhadada; Vivek Sagar; Pramod Kumar Gupta; Jarnail Singh Thakur; Madhu Gupta; Rachana Srivastava (Contemporary Clinical Trials Communications)
Introduction: Type 2 diabetes mellitus (T2DM) presents significant public health challenges in India, where unique genetic and phenotypic characteristics elevate susceptibility. Recent research highlights the interaction of genetic polymorphisms and dietary factors in T2DM management, forming the basis of personalised nutrition interventions. This study outlines the protocol for NUDGE clinical trial to evaluate the efficacy of gene-based dietary strategies compared to standard recommendations in T2DM management. Methods: The NUDGE trial is an exploratory, open-label, parallel-group, randomised controlled clinical trial conducted across healthcare settings in Chandigarh, India. A total of 300 participants diagnosed with T2DM will be randomised into intervention and control groups. The intervention group will receive personalised diet plans based on genetic polymorphisms (TCF7L2 and PPARG), anthropometric, and lifestyle data, while the control group follows standard dietary advice. Baseline and endline assessments will measure fasting blood glucose, HbA1c, anthropometric parameters, and adherence. Discussion: Primary outcomes focus on changes in FBG, while secondary outcomes include weight and blood pressure. Statistical analyses will evaluate gene-diet interactions and adherence to dietary plans. The trial aims to establish evidence for precision nutrition in T2DM by leveraging gene-diet interactions to tailor interventions. Findings will provide insights into the role of personalised nutrition in improving glycemic control. Conclusion: The NUDGE trial seeks to advance precision nutrition in T2DM management, paving the way for individualised dietary recommendations to mitigate disease progression and complications. Ctri reg no: CTRI/2021/09/036121 Clinical Trial Registry of India.